2022
DOI: 10.1002/adom.202102264
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Nanowire Architectures Self‐Assembled from Ultra‐Deep‐Blue Fluorene‐Based Conjugated Molecules toward Organic Light‐Emitting Diodes with CIEy = 0.06

Abstract: Organic conjugated molecules with a rigid rod‐like π‐backbone structure automatically and easily self‐assemble into an anisotropic nanostructure. However, supersecondary structures obtained from the hierarchical secondary self‐assembly of nanostructures have rarely been reported for non‐amphiphilic conjugated molecules. Here, a nanowire architecture as a supersecondary structure from an ultra‐deep‐blue fluorene‐based conjugated molecule (FCz‐C8‐Am) to improve the emission efficiency and stability is reported. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 70 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…Therefore, as an alternative to LD-1, CL-1 molecules are rationally designed and easily prepared via a one-step Suzuki reaction, as displayed in the Supporting Information (Scheme S1). 40 The chemical structures are confirmed by NMR analysis and single-crystal measurements (Figures S1 and S2). More interestingly, according to the theoretical simulation in Figure 2a, the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) energy levels of CL-1 molecules are calculated to be about −6.22 and −2.13 eV, respectively.…”
mentioning
confidence: 70%
See 4 more Smart Citations
“…Therefore, as an alternative to LD-1, CL-1 molecules are rationally designed and easily prepared via a one-step Suzuki reaction, as displayed in the Supporting Information (Scheme S1). 40 The chemical structures are confirmed by NMR analysis and single-crystal measurements (Figures S1 and S2). More interestingly, according to the theoretical simulation in Figure 2a, the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) energy levels of CL-1 molecules are calculated to be about −6.22 and −2.13 eV, respectively.…”
mentioning
confidence: 70%
“…Therefore, as showed in Figure , it is clear that the LD-1 molecules had emission peaks at 390 and 410 nm with a lasing peak at 410 nm, which are attributed to the intramolecular planar conformation and weak intermolecular π interaction . In this regard, similar to the discussion above, the twisted molecular conformation with an extremely weak intermolecular interaction may be useful to obtain excellent ultraviolet and deep-blue emission. , As displayed in Figure a, as expected, the diluted CL-1 solution had a maximum absorption peak at 326 nm, attributed to the intramolecular vibration band, which is consistent with previous works. ,, Due to the strong self-absorption induced by the millimeter-scale thickness, the optical spectral analysis of CL-1 single crystal is not provided here. It is easily found that the CL-1 single crystal also had robust ultraviolet and deep-blue emission under UV lamp 365 nm excitation (inset in Figure a).…”
mentioning
confidence: 99%
See 3 more Smart Citations